1998
DOI: 10.1093/qjmed/91.10.687
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum TSH in the investigation of patients presenting with thyroid enlargement

Abstract: In otherwise euthyroid patients presenting with thyroid enlargement, reduction in serum thyrotrophin (TSH) concentrations measured in a sensitive assay may be a marker of thyroid autonomy and may therefore indicate a benign underlying pathology. We investigated prospectively a cohort of 467 subjects presenting consecutively to our thyroid clinic with nodular or diffuse enlargement of the thyroid. Subjects were divided into those with normal (0.4-5.5 mU/l), low but detectable (0.1-0.39 mU/l) or undetectable (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…11,12,15 In addition, low TSH concentrations below the normal range are associated with a lower risk of thyroid malignancy. 9,12,16,17 In the present study we noted that the risk of malignancy increased in parallel with serum TSH concentrations in patients with thyroid nodules, a finding consistent with previous reports, and the association was restricted to thyroid nodules >1 cm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…11,12,15 In addition, low TSH concentrations below the normal range are associated with a lower risk of thyroid malignancy. 9,12,16,17 In the present study we noted that the risk of malignancy increased in parallel with serum TSH concentrations in patients with thyroid nodules, a finding consistent with previous reports, and the association was restricted to thyroid nodules >1 cm.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, preoperative serum TSH concentrations are higher in patients with more aggressive tumors, suggesting a potential role for TSH in the progression of differentiated thyroid cancer . In addition, low TSH concentrations below the normal range are associated with a lower risk of thyroid malignancy . In the present study we noted that the risk of malignancy increased in parallel with serum TSH concentrations in patients with thyroid nodules, a finding consistent with previous reports, and the association was restricted to thyroid nodules >1 cm.…”
Section: Discussionsupporting
confidence: 92%
“…In summary, many studies have attempted to confirm the relationship between the development of thyroid cancer and serum TSH level, and most have shown that an elevated TSH level is related to thyroid cancer. The elevated serum TSH level in patients with thyroid abnormalities is associated with thyroid cancer; even within the normal range, there is a higher risk of thyroid cancer among patients with a higher serum TSH level [9][10][11][12]. However, few studies have included only PTMC patients; therefore, the results have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that an elevated serum TSH level was associated with thyroid cancer [9][10][11][12][13], and one study suggested that the http://www.enm-kes.org serum TSH level was a novel predictor of malignancy [10]. However, another study showed that the serum TSH level was not elevated in papillary thyroid carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of serum TSH, which is a highly sensitive biochemical test for thyroid dysfunction, is recommended in the initial evaluation of patients presenting with thyroid nodules [9,23]. Encouragingly, several studies discovered an association of serum TSH and thyroid malignancy [12][13][14][15][16][17][24][25][26][27][28][29].…”
Section: Tsh and Likelihood Of Malignancymentioning
confidence: 99%